2008
DOI: 10.2167/beb425.0
|View full text |Cite
|
Sign up to set email alerts
|

Contexts for Learning: English Language Learners in a US Middle School

Abstract: Within the sociocultural theoretical framework that this paper adopts, learning, including second-language learning, is conceptualised as increasing participation in a community of practice. Thus it becomes of central importance to examine the nature of the community itself and the kinds of participatory opportunities that it supports or discourages. For it is through their engagement in the specific practices of their communities that students appropriate the knowledgeable skills that these practices involve.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The small body of research focused on the relations among beliefs and practices of teachers of DLLs has found positive relations between teachers’ beliefs about bilingualism/bilingual education (e.g., using the students’ home language in the classroom) and varied instructional practices (e.g., constructivist approaches, literacy practices, standards-based teaching) for school-age populations (Flores, 2001; Haneda, 2008; Rueda & Garcia, 1996; Vázquez-Montilla, Just, & Triscari, 2014). Of these studies, only Flores (2001) investigated teachers’ use of culturally and linguistically responsive strategies; however, a limitation of this study is that teachers self-reported their practices which may not accurately reflect what practices are implemented.…”
Section: Potential Influences On Language and Literacy Practices Withmentioning
confidence: 99%
“…The small body of research focused on the relations among beliefs and practices of teachers of DLLs has found positive relations between teachers’ beliefs about bilingualism/bilingual education (e.g., using the students’ home language in the classroom) and varied instructional practices (e.g., constructivist approaches, literacy practices, standards-based teaching) for school-age populations (Flores, 2001; Haneda, 2008; Rueda & Garcia, 1996; Vázquez-Montilla, Just, & Triscari, 2014). Of these studies, only Flores (2001) investigated teachers’ use of culturally and linguistically responsive strategies; however, a limitation of this study is that teachers self-reported their practices which may not accurately reflect what practices are implemented.…”
Section: Potential Influences On Language and Literacy Practices Withmentioning
confidence: 99%
“…It is unclear why teachers expected that they would need to devote more individual time and provide more peer assistance to the Polish student than the Auslan student. On one hand, this view is promising, considering that the literature on ESL education identifies peer collaboration and meaningful communication as optimal strategies for learning English (Gersten, 1999;Haneda, 2008;Lee, 2004;Mickan, 2007;Olivo, 2003) and it is encouraging to discover that the preservice teachers in this study independently suggested teaching strategies for ESL students that are considered effective in the literature. Although these strategies are useful for ESL students, it is likely that they would also be beneficial to deaf students who use Auslan.…”
Section: Discussionmentioning
confidence: 84%
“…Studies have shown that the best predictor of language acquisitionand consequently understanding of the content being taught -is when students have opportunities to practise English within meaningful interactions (Gersten, 1999;Haneda, 2008;Lee, 2004;Mickan, 2007). Strategies that allow ESL students to practise English include informal opportunities for meaningful discussion within the classroom (Olivo, 2003), collaborative learning (Oortwijn, Boekaerts, & Vedder, 2008), and encouraging students to practise writing for multiple contexts and multiple audiences (McCarthey & García, 2005).…”
Section: Teaching Strategies For Deaf and Esl Studentsmentioning
confidence: 99%
“…In North America, researchers have been examining various social, cultural, and political contexts in English learning among immigrant and ELL students (Haneda, 2008;Hancock, 2001;Kramsch, 1995;Liang, 2006;Saville-Troike, 1989;Spolsky, 1990). These contexts range from broad educational movements and policies to particular situations in the classroom, community, or home (Gándara & Rumberger, 2009;Moll & Whitmore, 1993;Taylor & Dorsey-Gaines, 1988;Valdés, 2001).…”
Section: Fan-lost In Institutionmentioning
confidence: 99%